Kemampuan Berpikir Kritis Matematis Dengan Model Pembelajaran EXO OLO TASK - Apria Randi Saputra; Tasnim Rahmat (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
The low students' avarage number of mathematical critical thinking skills in class VIII SMPN 1 Candung ranged from 82.14% to 89.29%. To overcome this problem, researchers tried to conduct research by applying the EXO OLO TASK learning model in learning mathematics. This type of research is pre-experimental research with the research design The Static Group Comparison Design. The population in this study were all students of class VIII SMPN 1 Cawang. The samples in this study were students of class VIII.2 as the experimental class and VIII.1 as the control class. The instrument in this study was a test of students' mathematical critical thinking skills in the form of an essay test. The results of the study using the t-test obtained t_count=1.92 > t_table=1.674, so H0 was rejected. For Minitab software testing at a significant level of a = 0.05, Pvalue = 0.002 is obtained, meaning Pvalue <a, so H0 is also rejected. So it can be concluded that students' mathematical critical thinking skills using the EXO OLO TASK learning model are better than students' mathematical critical thinking abilities using conventional learning in class VIII SMPN 1 Cdungung.